2020
DOI: 10.1088/1361-665x/aba63c
|View full text |Cite
|
Sign up to set email alerts
|

Surface Textures for Stretchable Capacitive Strain Sensors

Abstract: Advances in smart materials and electronics have enabled compliant sensing systems mimicking nature. In structural health monitoring (SHM) applications, the technology still lacks accuracy in tracking measurements over large geometries. Herein we report a facile fabrication for a compliant sensor based on an elastomeric capacitive sensor technology, augmented with a scalable surface texture inspired by various grid geometries. Texture designs are selected to direct, and therefore improve, the strain sensing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Briefly, the Poisson's ratio ν of an untextured dielectric film was measured with two digital cameras (FASTCAM SA-Z and Photron) by subjecting a specimen to a 30% uniaxial strain applied at 80 µm/s. Note that 30% is the maximum strain level used in this study, consistent with experimental tests conducted on free-standing SECs in [21] and with levels expected for the application [6], and that a characterization of the electromechanical model at higher strain levels is left to future work. A 7 × 7 mm 2 region around the transverse centerline was defined as the region of interest (red rectangle in Figure 3a) to extract the Poisson's ratio.…”
Section: • Sec Sensor Modelsupporting
confidence: 77%
See 4 more Smart Citations
“…Briefly, the Poisson's ratio ν of an untextured dielectric film was measured with two digital cameras (FASTCAM SA-Z and Photron) by subjecting a specimen to a 30% uniaxial strain applied at 80 µm/s. Note that 30% is the maximum strain level used in this study, consistent with experimental tests conducted on free-standing SECs in [21] and with levels expected for the application [6], and that a characterization of the electromechanical model at higher strain levels is left to future work. A 7 × 7 mm 2 region around the transverse centerline was defined as the region of interest (red rectangle in Figure 3a) to extract the Poisson's ratio.…”
Section: • Sec Sensor Modelsupporting
confidence: 77%
“…Previous work has demonstrated that the Poisson's ratio of the thin film was tunable by augmenting the sensor with a texture. In particular, a diagrid-like pattern was experimentally shown to enhance directionality and to improve the experimental gauge factor by 30% [21]. The current paper extends the previous study to auxetic patterns, known to yield a negative Poisson's ratio [22,23].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations